Digital marketing strategies in expanding the market for MSME creative products in Indonesia—state of art - Lubis, Ulfi Sartika; Wulandari, Novita; Wahyudi, Iwan; Widiyanto, Andika; Wibowo, Edwin Agung; Hakim, Lukmanul; Apriyansyah, Bahalwan; Hardiati, Neni; Swastika, Anggun Yulvira; Meyzia, Bunga (Frontiers in Communication, 2025)
Digital marketing strategy is the planning and actions taken by companies or individuals to utilize digital technology to market products or services effectively and efficiently to target markets. In this strategy, companies use various digital channels such as social media, search engines, email marketing, websites, or e-commerce to achieve marketing objectives, including increasing brand awareness, attracting new customers, and boosting sales and customer loyalty. However, challenges in using digital marketing still exist due to the digital literacy gap among creative product practitioners. This study reviews digital marketing for creative products, including social media marketing, search engine marketing, influencer marketing, email marketing, and content marketing. Using Systematic Reviews and Meta-Analysis (PRISMA) method, 22 articles from leading sources such as MDPI, Wiley, ScienceDirect, and IEEE Xplore were analyzed. The objectives of this study are to determine (1) what the definitions of digital marketing strategies and the creative product market are. (2) Which countries have implemented digital marketing in the creative market for SMEs? (3) Who is involved, and how familiar are SMEs with the creative product market? (4) What strategies are used in digital marketing in Indonesia? How is it implemented, what are the challenges, and what is the level of success? (R5): What are the future research and recommendations for digital marketing in expanding the creative market? Future research directions include the application of AI and technology for automated content creation for creative product practitioners, strengthened digital education and literacy, and community-based campaigns that foster collaboration among local creators to build a mutually supportive ecosystem in the digital world.